Stress Varies Along the Social Density Continuum - Love, Jay; Zelikowsky, Moriel (Frontiers in Systems Neuroscience, 2020)
Social stress is ubiquitous in the lives of social animals. While significant research has aimed to understand the specific forms of stress imparted by particular social interactions, less attention has been paid to understanding the behavioral effects and neural underpinnings of stress produced by the presence and magnitude of social interactions. However, in humans and rodents alike, chronically low and chronically high rates of social interaction are associated with a suite of mental health issues, suggesting the need for further research. Here, we review literature examining the behavioral and neurobiological findings associated with changing social density, focusing on research on chronic social isolation and chronic social crowding in rodent models, and synthesize findings in the context of the continuum of social density that can be experienced by social animals. Through this synthesis, we aim to both summarize the state of the field and describe promising avenues for future research that would more clearly define the broad effects of social interaction on the brain and behavior in mammals.